Breast Reconstruction in the Social Media Age. (18th August 2020) - Nguyen, Jonathan; Thompson, Peter; Losken, Albert
Abstract: Background: The internet and social media are sources of information regarding breast reconstruction, which can educate and influence patients. Objectives: This study aimed to evaluate internet and social media usage by breast reconstruction patients and its impact on patients. Methods: Eighty-six breast reconstruction patients over a 7-month period answered an anonymous survey, which queried demographics, reconstruction type, internet usage, social media usage, expectations, and impact on decisions. Fisher's exact test was performed to evaluate the use of social media. Results: Overall, 95% of patients used the internet for breast reconstruction information. The information was found to be easy to understand by 70% of patients, helpful by 76%, and trustworthy by 60%. The information influenced decisions regarding procedure by 23% of patients, regarding surgeon by 23%, and regarding hospital by 22%. Social media was used by 71% of the patients; 62% of patients found it easy to understand, 57% found it helpful, and 48% found it trustworthy. The information influenced decisions regarding procedure by 16% of patients, regarding surgeon by 11%, and regarding hospital by 10%. Twenty-six percent of women expected their final breast reconstruction to look better than their premastectomy breasts, 55% as good or similar, and 12% reported appearance to be unimportant. Women found social media information to be less helpful than internet information. There was no significant association between expectations and social media vs no social media usage. Conclusions: Patients who undergo breast reconstruction use the internet and social media as sources of information. Although the information is generally trusted, it does not seem to heavily influence patient decision-making. Providers remain patients' main source of information, and need to direct patients to high-quality and accessible resources.